COMPARATIVE RESEARCH ON EMPLOYEE COMMITMENT BETWEEN PART TIME AND FULL TIME WORKERS AT STARBUCKS MANADO TOWN SQUARE - Lendo, Octaviany Pricillia; Pangemanan, Sifrid S.; Rumokoy, Farlane S. (FEB Universitas Sam Ratulangi Manado, 2018)
Abstract: In order to make the job running well, every employee must have their own commitment for working on the company. Employee commitment is viewed as being a key prerequisite for the effective execution of projects, operational processes and the successful implementation of organizational change programs. This study is expected to give input to the company especially regarding with the full time and part time employee and how to make them commit with the job and organization. The sample size of this research is 30 employees that currently working in Starbucks Manado Town Square and using T-Test Method. Based on the result of this research, there is significant difference on Employee commitment measured by Motivation, there is significant difference on Employee commitment measured by Responsibility, there is no significant difference on Employee commitment measured by Achievement, there is significant difference on Employee commitment measured by Personal Life. So, based on the findings in this research, there are some recommendations for Starbucks Manado Town Square. Starbucks Manado Town Square should pay attention to all of the employees so they can maintain their commitment.Keywords: employee commitment, human resource management, motivation, responsibility, achievement, personal life, t-test method.